1990
DOI: 10.3354/dao008171
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance in a non-hemolytic Streptococcus sp. isolated from cultured yeltowtail Seriola quinqueradiata

Abstract: The antibacterial activities of 19 chemotherapeutic agents were tested against 370 strains of a non-hemolytic Streptococcus sp. pathogenic for a marine fish, the yellowtail Seriola quinqueradiata.The strains were isolated from cultured yellowtail in 1986 and 1987. Sixty-two of the tested strains showed resistance to macrolide antibiotics (MLs), lincomycin (LIM), tetracycline (TC), and chloramphenicol (CP). These resistant strains were classified into intermediate-and high-level resistance to MLs, LIM, TC, or C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 5 publications
(4 reference statements)
0
44
0
Order By: Relevance
“…Macrolide antimicrobials are not approved for administrating to Japanese flounder in Japan, but they have been used for treating streptococcicosis causing by Lactococcus garvieae in yellowtail Seriola quinqueradiata for many years. Several published works showed that L. garvieae strains isolated from yellowtail carried transferable R-plasmid on which erm(B) and tet (S) were integrated (Aoki et al, 1990;Maki et al, 2008). In addition, L. garvieae is also one of the pathogens causing streptococcicosis in cultured Japanese flounder (Fukuda, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Macrolide antimicrobials are not approved for administrating to Japanese flounder in Japan, but they have been used for treating streptococcicosis causing by Lactococcus garvieae in yellowtail Seriola quinqueradiata for many years. Several published works showed that L. garvieae strains isolated from yellowtail carried transferable R-plasmid on which erm(B) and tet (S) were integrated (Aoki et al, 1990;Maki et al, 2008). In addition, L. garvieae is also one of the pathogens causing streptococcicosis in cultured Japanese flounder (Fukuda, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of multiple drug-resistant strains has indicated future problems in controlling the pathogen (Aoki et al 1990). Recently, oral and injectable vaccines against L. garvieae infection in Seriola quinqueradiata have been developed and commercialized in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…The extensive use has led to an increase in drug resistant strains among fish pathogens. A transferable R plasmid has been suggested to be responsible for the drug resistance of several fish pathogenic bacteria including Aeromonas hydrophila (1), Aeromonas salmonicida (4), Edwardsiella tarda (7), Enterococcus seriolicida (9,18), and Vibrio anguillarum (5). Thus, the spread of R plasmids encoding multiple drug resistance has made chemotherapy of bacterial infections difficult in many fish farms (8).…”
mentioning
confidence: 99%